PELATIHAN “ENGLISH FOR TOURISM” PADA PELAKU UMKM DI DAERAH WISATA KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Sari, Erini Junita; Hanifah, Hanifah (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service program was designed to strengthen the English communication abilities of SME business owners in the tourism sites  in Banjar Regency, South Kalimantan. The initiative responds to the limited English skills that often restrict the business owners from delivering quality service to international visitors. The three-day training combined interactive lectures, role-playing activities, and hands-on practice in simulated tourism situations. The program resulted in increased confidence and improved basic English skills among participants, particularly in greeting tourists, giving directions, and describing local attractions.